(untitled) (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2023)
This paper explores the topic of consumer culture and its implications for environmental degradation, opening a dialogue to the need for a new productive rationality. The problem that guides the research is: to what extent does the culture of consumption established in society aggravate the degradation of the environment and induce dialogue on new ways of thinking about the economic process? The general objective of the research is, using exploratory methodology and bibliographic technique, to analyze the role of consumer culture in the environmental crisis installed in the 21st century, aiming at the study of alternative ways of thinking about consumer relations. As a conclusion, it is inferred that, while consumerism induces social relations and there is no more balanced form of consumption, environmental degradation will continue to reach high rates, which refers to the need to adopt an ecological awareness and productive rationality, so that it is possible to preserve current and future generations.